iTRAQ-Based Quantitative Proteomic Analysis of a Toxigenic Dinoflagellate Alexandrium catenella and Its Non-toxigenic Mutant Exposed to a Cell Cycle Inhibitor Colchicine - Zhang, Shu-Fei; Zhang, Yong; Lin, Lin; Wang, Da-Zhi (Frontiers in Microbiology, 2018)
Paralytic shellfish toxins (PSTs) are a group of potent neurotoxic alkaloids mainly produced by marine dinoflagellates and their biosynthesis is associated with the cell cycle. Study shows that colchicine can cease cell division and inhibit PST production of dinoflagellates. However, the molecular mechanism behind this linkage is unknown. Here, we applied the iTRAQ-based proteomic approach to investigate protein expression profiles of a toxigenic dinoflagellate Alexandrium catenella (ACHK-T) and its non-toxigenic mutant (ACHK-NT) when treated with colchicine. The results showed that the cell cycles of both strains were arrested at the G1 phase by colchicine, and the toxin biosynthesis of ACHK-T was inhibited. Among 6,988 proteins identified, 113 and 253 proteins were differentially expressed in the colchicine-treated ACHK-T and ACHK-NT respectively compared with their non-colchicine treatments. Proteins involved in reactive oxygen species scavenging and protein degradation were up-regulated in both strains while proteins participating in photosynthetic pigment biosynthesis and nitrogen metabolism presented different expressions. Nitrate reductase and glutamine synthetase were altered insignificantly in the colchicine-treated ACHK-T while both of them were remarkably down-regulated in the colchicine-treated ACHK-NT, suggesting a feedback regulation between PST production and nitrogen metabolism in ACHK-T. Nitrogen originally for PST biosynthesis might be reallocated to photosynthetic pigment biosynthesis in the colchicine-treated ACHK-T. 55 homologs of seven toxin-related proteins were obtained; however, they altered insignificantly in both colchicine-treated strains, suggesting that toxin biosynthesis might be post-translationally regulated. Our study provided new insights into toxin biosynthesis in marine dinoflagellates.